Socioeconomic and work related determinants of pregnancy outcome in southern Thailand - Tuntiseranee, P. (BMJ Group, 1999)
STUDY OBJECTIVE: To examine the effect of socioeconomic status on pregnancy outcome in an urbanised area in a rapidly developing country. METHODS: A cohort of 1797 pregnant women who attended antenatal care clinics at the two 700 bed hospitals in Hatyai city was recruited from September 1994 to November 1995. The pregnant women were followed up from the 17th week of gestation until delivery. The socioeconomic indicators selected were family socioeconomic status, maternal education, maternal occupation, family income and work exposure characteristics based upon Karasek's job content questionnaires. Pregnancy outcomes were birth weight, low birth weight, small for gestational age and preterm delivery. MAIN RESULTS: Mean birth weight correlated with socioeconomic status and income but after adjustment for parity, maternal age and height, weight at delivery day, baby sex, obstetrical complications and antenatal care utilisation, only family income remained correlated with birth weight. No association with any socioeconomic status indicators was found when using dichotomous outcome (low birth weight, small for gestational age or preterm delivery). Only high psychological job demand was associated with small for gestational age. Confounder adjustment indicated that the observed social status differences in pregnancy outcomes were mainly attributable to mother's characteristics and antenatal service use. CONCLUSIONS: Socioeconomic indicators alone were not associated with reduced fetal growth or preterm delivery in this study, which recruited mainly lower or middle class women. Karasek's psychological job demand was only weakly correlated with small for gestational age infant.